1999
DOI: 10.1021/jf9810158
|View full text |Cite
|
Sign up to set email alerts
|

Carotene, Tocopherol, and Ascorbate Contents in Subspecies ofBrassica oleracea

Abstract: Cruciferous vegetables contain high levels of vitamins that can act as antioxidants, compounds that may protect against several degenerative diseases. The edible portions of 50 broccoli and 13 cabbage, kale, cauliflower, and Brussels sprouts accessions were assayed to determine variation in alpha-carotene, beta-carotene, alpha-tocopherol, gamma-tocopherol, and ascorbate contents within and between subspecies of Brassica oleracea. Ascorbate content was estimated in fresh samples using HPLC. Tissues for carotene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
195
5
14

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(240 citation statements)
references
References 34 publications
(44 reference statements)
19
195
5
14
Order By: Relevance
“…Similarly, all the interactions (C × S, C × P, S × P and C × S × P) were also significant. Similar cultivar dependent as well as seasonal dependent significant variation was also observed by Balouchi et al (2011), Koh et al (2009), Kurilich et al (1999, Rosa and Rodrigues (2001), ), Singh et al (2007 and Vallejo et al (2003) in various phytochemicals such as glucosinolates, vitamin C, phenolics, flavonoids, free sugars, however this is the first report that describes such variations (genotypic, seasonal as well as parts) in term of fatty acid composition in broccoli.…”
Section: Results and Discussion 1 Fatty Acid Compositionsupporting
confidence: 85%
“…Similarly, all the interactions (C × S, C × P, S × P and C × S × P) were also significant. Similar cultivar dependent as well as seasonal dependent significant variation was also observed by Balouchi et al (2011), Koh et al (2009), Kurilich et al (1999, Rosa and Rodrigues (2001), ), Singh et al (2007 and Vallejo et al (2003) in various phytochemicals such as glucosinolates, vitamin C, phenolics, flavonoids, free sugars, however this is the first report that describes such variations (genotypic, seasonal as well as parts) in term of fatty acid composition in broccoli.…”
Section: Results and Discussion 1 Fatty Acid Compositionsupporting
confidence: 85%
“…The HPLC condition for the estimation DL-α-tocopherol was adopted as described in [14] with some modification.…”
Section: Hplc Analysismentioning
confidence: 99%
“…[2][3][4] Moreover, epidemiological studies have revealed the potential of Brassica vegetables to reduce the risk of cardiovascular diseases and some types of cancer. 5) Kale is a leafy vegetable belonging to Brassica plants. The total polyphenol content in edible parts of kale has been reported to be higher than that of other Brassica vegetables such as califlower and broccoli, 6) and kale has therefore gained increased attention as a source of beneficial effects related to these substances.…”
mentioning
confidence: 99%